Konstrukcija identitete materinstva - Stermecki, Lidija (Monitor ISH, 2005)
The construction of the identity of motherhood. The paper is based on a content and discourse analysis of 66 texts, submitted for the short-story competition organised by the magazine Ona (She) on the theme of Her Story - Birth. While most women appear to be quick to adopt the discourse practices forced upon them by society, in fact identifying with the most frequent female role of a mother, some texts do reveal difficulties and insecurities in establishing the identity of motherhood, or even strong resistance to the myths and ideals enforced by the society. Since the institution of motherhood is one of the prime movers and preservers of the patriarchal system, any opposition to the enforced social/gender roles has an important role in discovering the true identity of women: aware of the latter, they will demand their right to mental, physical, and intellectual integrity.
Keywords: materinstvo; identiteta; spolna identiteta; konstrukcija identitete; woman; ženske; ženske revije